Community pharmacy advanced adherence services for children and young people with long-term conditions: A cross-sectional survey study - Zahra Alsairafi; Julie Mason; Natasha Davies; Molly Dennis; Gabrielle Pilgrim; Neera Goel; Asma Yahyouche; Zahraa Jalal (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: The aim of this study was to investigate the provision of community pharmacy services to children and young people with a focus on advanced services such as medicines use review. Perceptions and experiences of community pharmacists, pharmacy staff, young people and their parents or carers on the provision of such services were also explored. Methods: Four different cross-sectional, self-administered questionnaires were distributed in parallel to pharmacists, pharmacy staff members, children and young people and parents in the United Kingdom. Results: An outline of pharmacist's current involvement with children and young people was provided by 92 pharmacists. A different group of 38 community pharmacists and 40 non-pharmacist members of pharmacy staff from a total of 46 pharmacies provided information and views on the conduct of Medicines use review with children and young people. Experiences of advanced pharmacy service provision were collected from 51 children and young people and 18 parents. Most pharmacists offered public health advice to children and young people (73/92; 79.3%) and even more (83/92; 90.2%) reported that they often interacted with children and young people with long-term condition. Despite their high levels of interaction, and a majority opinion that medicines use reviews could benefit children (35/38; 92.1%), the number of pharmacies reporting to have conducted medicines use reviews with children was low (5/41). Pharmacists perceived the main barriers to recruitment as consent (17/29; 58.6%), guideline ambiguity (14/29; 48.3%) and training (13/29; 44.8%). A considerable proportion pharmacists (12/29; 41.4%) and other personnel (14/33; 42.4%) working in community pharmacies were unaware that children were potentially eligible for medicines use reviews. Only 29.4% of the 51 children and young people participants had received advice about their long-term condition from a pharmacist and the majority (46/51; 90.2%) had not taken part in an advanced service focused on adherence. Conclusions: While general engagement with children and young people appears high from the pharmacist's perspective, advice specific to children and young people with long-term conditions and the provision of advanced services in this group remains a challenge.